ANALISIS STRATEGI COMMUNITY DEVELOPMENT PADA PROGRAM CSR RUMAH KREATIF TAMIANG OLEH PT. PERTAMINA EP RANTAU FIELD - Humaedi, Sahadi; Raharjo, Santoso Tri; Ardiansyah, Raka Putra (Universitas Padjadjaran, 2025)
Kabupaten Aceh Tamiang merupakan salah satu kabupaten dengan populasi penyandang disabilitas terbesar di Provinsi Aceh, dengan sekitar 616 orang diantaranya tergolong dalam kategori miskin dan masih terdapat potensi sumberdaya manusia yang belum diberdayakan secara optimal. Penelitian ini mengkaji strategi pemberdayaan komunitas dalam program Corporate Social Responsibility (CSR)Rumah Kreatif Tamiang oleh PT. Pertamina EP Rantau Field yang memanfaatkan penyandang disabilitas dalam pengelolaan limbah dari 60 Usaha Mikro, Kecil, dan Menengah di Galeri Ajang Ambe. Melalui studi literatur dari berbagai sumber yangrelevan dengan topik terkait. Ditemukan bahwa Rumah Kreatif Tamiang membantu dalam pengembangan potensi masyarakat difabel di Aceh dengan menginisiasikan program yang meliputi pendidikan serta pelatihan secara inklusif. Hasil penelitian ini menunjukkan bahwa program Corporate Social Responsibility (CSR) Rumah Kreatif Tamiang berhasil dalam meningkatkan kemandirian serta kesetaraan yangberdampak pada meningkatnya perekonomian bagi penyandang difabel dalam kategori miskin di Kabupaten Aceh Tamiang. Aceh Tamiang Regency is one of the districts with the largest population of people with disabilities in Aceh Province, with around 616 people belonging to the poor category and there is still potential human resources that have not been utilized optimally. This research examines community empowerment strategies in the Tamiang Creative House Corporate Social Responsibility (CSR) program by PT. Pertamina EP Rantau Field which utilizes people with disabilities in waste management from 60 Micro, Small, and Medium Enterprises in the Ambe Ajang Gallery. Through literature studies from various sources relevant to related topics. It was found that Tamiang Creative House helped in developing the potential of the disabled community in Aceh by initiating programs that included inclusive education and training. The results of this research show that the Tamiang Creative House Corporate Social Responsibility (CSR) program has succeeded in increasing independence and equality, which has improved the economy for people with disabilities in the poor category in Aceh Tamiang Regency. Aceh Tamiang Regency is one of the districts with the largest population of people with disabilities in Aceh Province, with around 616 people belonging to the poor category and there is still potential human resources that have not been utilized optimally. This research examines community empowerment strategies in the Tamiang Creative House Corporate Social Responsibility (CSR) program by PT. Pertamina EP Rantau Field which utilizes people with disabilities in waste management from 60 Micro, Small, and Medium Enterprises in the Ambe Ajang Gallery. Through literature studies from various sources relevant to related topics. It was found that Tamiang Creative House helped in developing the potential of the disabled community in Aceh by initiating programs that included inclusive education and training. The results of this research show that the Tamiang Creative House Corporate Social Responsibility (CSR) program has succeeded in increasing independence and equality, which has improved the economy for people with disabilities in the poor category in Aceh Tamiang Regency.